A RETROSPECTIVE ANALYSIS OF THE PREVALENCE OF ECHINOCOCCOSIS IN THE REPUBLIC OF KAZAKHSTAN - Shabdarbayeva, G.; Yalysheva, S. (Scientific Journal of Pedagogy and Economics, 2020)
Echinococcosis is a zoonotic helminthiasis of humans and animals caused by Echinococcus granulosus tapeworm. Echinococcosis is often expensive and complicated to treat and may require extensive surgery or prolonged drug therapy. In addition, echinococcosis causes serious annual livestock production losses. More than 1 million people are affected with echinococcosis at any one time. Kazakhstan is one of the countries with adverse epidemiological situation for echinococcosis. The aim of the study is a retrospective investigation of changes in the incidence of cystic echinococcosis in the Republic of Kazakhstan. Scientific articles on prevalence and data from scientific reports were analyzed. Current situation has changed and remains complicated. Echinococcosis is present in all regions of the country; however, the most endemic area is the south of Kazakhstan, which is a large livestock husbandry center. The highest rates are observed in South Kazakhstan (Turkestan), Zhambyl, Almaty regions. The least prevalence of echinococcosis is in Pavlodar, Kostanai region and Nur-Sultan city. In general, from 1984 to 2016 the incidence rate in the country has grown by more than 5 times. Since 2007, there has been a gradual decrease in the number of newly registered cases. However, in endemic areas of the south, rates remain high. Existing accounting systems for patients with echinococcosis and statistical data cannot fully reflect the real number of people infected with echinococcosis, since only surgical cases are taken into account. Monitoring of the natural foci of Echinococcosis required for taking coordinated actions to combat disease. Cooperation between medical and veterinary specialists is necessary in order to get a full extent of the situation with zoonotic helminthiases.